2022
DOI: 10.3390/v14122807
|View full text |Cite
|
Sign up to set email alerts
|

Tropism and Infectivity of Pandemic Influenza A H1N1/09 Virus in the Human Placenta

Abstract: Influenza virus infection in pregnant women may put the fetus at higher risk; however, to date, there has been no detailed research about the expression of influenza virus receptors in the human placenta. We employed the lectin staining technique, which is a classic influenza virus receptor research method for studying the distribution of viral receptors in the human placenta. In addition, we examined the susceptibility of the human placenta to H1N1/09, by detecting viral proteins and RNA at different time poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The potential effects of the influenza virus on the mother and fetus are not well understood. Since influenza viruses are rarely passed through the placenta, the infection is more likely to cause preterm birth through other mechanisms, such as maternal fever and inflammatory responses (49)(50)(51). Elevated levels of pro-inflammatory cytokines in the body can cause immune perturbation, leading to the sluggish establishment of immune tolerance and excessive inflammation, which in turn affects placental function (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The potential effects of the influenza virus on the mother and fetus are not well understood. Since influenza viruses are rarely passed through the placenta, the infection is more likely to cause preterm birth through other mechanisms, such as maternal fever and inflammatory responses (49)(50)(51). Elevated levels of pro-inflammatory cytokines in the body can cause immune perturbation, leading to the sluggish establishment of immune tolerance and excessive inflammation, which in turn affects placental function (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Transplacental transmission of the 2009 AH1N1 virus was alleged in some cases, but definitive evidence was not available at the time. A recent study by Xiao et al concluded that the human placenta can be infected [ 6 , 7 ]. Nonetheless, data from the AH1N1 pandemic highlight that influenza during pregnancy escalates the likelihood of unfavorable pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%